Strategi Rekrutmen Dan Seleksi Di Era VUCA - M. Firdaus Tsani; Thijanul Aroby; Prata Vitha Maysha Rado; Mochammad Isa Anshori (Institut Teknologi dan Bisnis (ITB) Semarang, 2023)
The VUCA (Volatile, Uncertain, Complex, Ambiguous) era has significantly changed the business landscape, forcing organizations to change their approach to recruitment and selection strategies. In this context, this research explores how organizations can adapt their recruitment and selection practices to address the challenges of the VUCA era. This study presents an in-depth literature review of recruitment and selection strategies relevant to the VUCA era. We highlight a shift from an emphasis on technical skills toward assessing adaptability skills, situational leadership, and the ability to collaborate in multidisciplinary teams. In addition, this research considers the use of technology such as data analysis and artificial intelligence in the recruitment and selection process. We illustrate its usefulness in identifying candidates that have the potential to deal with uncertainty and ambiguity. The results show that organizations need to change their recruitment and selection paradigm to be more responsive to the VUCA era. They should focus on identifying candidates who not only have the necessary technical skills but also have strong adaptability, problem-solving and collaboration abilities. Technology can be a valuable tool in assisting this process. In conclusion, recruitment and selection strategies in the VUCA era must follow market development trends and prioritize attributes that are relevant to the challenges faced by the organization. In this way, organizations can build a workforce that is ready to face uncertainty and achieve long-term success.